2006
DOI: 10.1065/espr2006.01.295
|View full text |Cite
|
Sign up to set email alerts
|

Benzotriazoles, Alkylphenols and Bisphenol A in Municipal Wastewaters and in the Glatt River, Switzerland

Abstract: The investigated contaminants occur at quantitatively measurable but varying concentrations in municipal wastewaters and in the Glatt River reflecting their ubiquitous input into wastewaters and their different behaviour during biological wastewater treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
166
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(190 citation statements)
references
References 34 publications
20
166
4
Order By: Relevance
“…5-TTri was found less persistent than BT under aerobic conditions. It is reported that the removal efficiencies of 5-TTri were also much higher than BT in conventional activated sludge treatment plants (Voutsa et al, 2006;Weiss et al, 2006).…”
Section: Effects Of Redox Conditions On Degradation Of Bts In Aquifersmentioning
confidence: 97%
See 2 more Smart Citations
“…5-TTri was found less persistent than BT under aerobic conditions. It is reported that the removal efficiencies of 5-TTri were also much higher than BT in conventional activated sludge treatment plants (Voutsa et al, 2006;Weiss et al, 2006).…”
Section: Effects Of Redox Conditions On Degradation Of Bts In Aquifersmentioning
confidence: 97%
“…They are widely used as corrosion inhibitors in dishwashing detergents, brake fluids, motor vehicle antifreeze and aircraft deicing fluids (Janna et al, 2011). Benzotriazoles (BTs) including BT and 5-TTri have been widely detected in effluents of wastewater treatment plants around the world at concentrations up to 3.4 μg/L Hollingsworth et al, 2005;Voutsa et al, 2006;Weiss et al, 2006), in sediment and sludge at concentrations up to 198 ng/g (Zhang et al, 2011). Much higher concentrations of up to 126 mg/L for BT and 17 mg/L for 5-TTri have been found in groundwater from airport locations due to its heavy use as an antifogging agent (Cancilla et al, 1998(Cancilla et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increasing attention has been paid to the removal of various emerging contaminants including BTs and UV filters in WWTPs (Hollingsworth et al, 2005;Giger et al, 2006;Voutsa et al, 2006;Li et al, 2007), mainly due to increasing environmental awareness and wastewater reuse requirements. WWTPs are normally designed to eliminate solids, suspended particulates, nutrients, and dissolved biodegrable organic matter, but not specifically designed for the removal of emerging contaminants such as BTs and UV filters.…”
Section: Introductionmentioning
confidence: 99%
“…WWTPs are normally designed to eliminate solids, suspended particulates, nutrients, and dissolved biodegrable organic matter, but not specifically designed for the removal of emerging contaminants such as BTs and UV filters. Limited studies have shown incomplete removal in conventional WWTPs, with removal efficiencies in the range of 13e62% for benzotriazole (BT), 11e74% for 5-methyl-benzotriazole (5-TTri), 28e96% for benzophenone-3 (BP-3), 18e82% for 3-(4-methylbenzylidene)camphor (4-MBC), 40 to >99% for octyl 4-methoxycinnamate (OMC), and 36 to >99% for octocrylene (OC) (Balmer et al, 2005;Hollingsworth et al, 2005;Giger et al, 2006;Plagellat et al, 2006;Voutsa et al, 2006;Weiss et al, 2006;Li et al, 2007). In order to improve their removal rates, we need to explore the mechanisms involved in the treatment processes (Langford and Lester, 2003).…”
Section: Introductionmentioning
confidence: 99%